Glasserâs disease in swine in Batam Island, Riau Province - Priadi, Adin; Natalia, L; Poernomo, S (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Glasserâs disease or Haemophilus parasuis in swine causes a considerable economic losses. This disease decreases farm production due to high mortality. In a field investigation, H. parasuis serotype 12 was isolated from the lung of a ten week old post weaning pig suffering from pneumonia in Bulan island, Riau Province. The isolation of H. parasuis in a pig herd showing increasing mortality is the first reported in Indonesia. Antibiotic sensitivity test using disc diffusion methods, showed that the isolate was sensitive to bacitracin, baytril, erythromycin and was resistance to neomycin, kanamycin, doxycyclin, ampicillin and sulphamethoxazol-trimethoprim. Vaccination in weaned piglet using commercial inactivated vaccine was monitored using Enzyme-linked immunosorbent assay (ELISA). Crude extract of culture H. parasuis serotype 12 was used as the ELISA coating antigen. There was no significant immune response detected by ELISA 3 months after vaccination. Â  Key words: Glasserâs disease, swine, drug sensitivity, ELISA